Hadith #4901 - Sunan Abi Dawud - Abu 'Amir al-'Aqdi عبد الملك بن عمرو القيسي أبو عامر العقدي; Abu Hurairah; Sulaiman bin Bilal al-Taymi سليمان بن بلال التيمي; Uthman bin Salah al-Sahmi عثمان بن صالح بن صفوان السهمي (Sunan Abi Dawud)
I heard the Messenger of Allah (ﷺ) say: There were two men among Banu Isra’il, who were striving for the same goal. One of them would commit sin and the other would strive to do his best in the world. The man who exerted himself in worship continued to see the other in sin. He would say: Refrain from it. One day he found him in sin and said to him: Refrain from it. He said: Leave me alone with my Lord. Have you been sent as a watchman over me? He said: I swear by Allah, Allah will not forgiv
Grade: Sahih